Neuromuscular Ultrasound for Peripheral Neuropathies - Baute Penry, Vanessa; Cartwright, Michael S. (Seminars in Neurology, 2019)
Neuromuscular ultrasound (NMUS) is a diagnostic technique that is now commonly used to complement electrodiagnostic studies when evaluating for suspected peripheral nerve pathology. The use of NMUS has been described in focal mononeuropathies, polyneuropathies, and motor neuron disease. This article provides a general overview of NMUS for the evaluation of peripheral neuropathies based on clinical practice guidelines, primary literature, and expert opinion. The characteristic changes detected by NMUS are described in focal mononeuropathies (including entrapment and other causes), polyneuropathies (including demyelinating and axonal processes), and motor neuron disease.
Keywords: ultrasound; carpal tunnel syndrome; entrapment; polyneuropathy; amyotrophic lateral sclerosis